RNA methylation and cancer treatment - Yang, Baochen; Wang, Jing-Quan; Tan, Yao; Yuan, Runzhu; Chen, Zhe-Sheng; Zou, Chang (Pharmacological research, 2021)
To this date, over 100 different types of RNA modification have been identified. Methylation of different RNA species has emerged as a critical regulator of transcript expression. RNA methylation and its related downstream signaling pathways are involved in plethora biological processes, including cell differentiation, sex determination and stress response, and others. It is catalyzed by the RNA methyltransferases, is demethylated by the demethylases (FTO and ALKBH5) and read by methylation binding protein (YTHDF1 and IGF2BP1). Increasing evidence indicates that this process closely connected to cancer cell proliferation, cellular stress, metastasis, immune response. And RNA methylation related protein has been becoming a promising targets of cancer therapy. This review outlines the relationship between different types of RNA methylation and cancer, and some FTO inhibitors in cancer treatment. [Display omitted]